PENGARUH LOKASI TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PERUMAHAN THE ANGGANA PT ADHI PERSADA PROPERTY JAKARTA - Bongsu Saragih (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This study aims to determine and analyze the influence of location on purchasing decisions, knowing and analyzing the influence of location on customer satisfaction, knowing purchasing decisions on customer satisfaction, knowing the effect of location on customer satisfaction through customer decisions. The analysis shows that location influences purchasing decisions, which means that the more location strategy can improve purchasing decisions. Location affects customer satisfaction, which means that locations that are easily accessible can increase customer satisfaction. Purchasing decisions affect customer satisfaction, which means that consumers will feel satisfied if there is compatibility. Location influences customer satisfaction through purchasing decisions, which means that strategic location can increase customer satisfaction if purchasing decisions are made rationally.